2016
DOI: 10.1155/2016/5027243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of La and Ce Addition on the Modification of Al-Si Based Alloys

Abstract: This study focuses on the effects of the addition of rare earth metals (mainly lanthanum and cerium) on the eutectic Si characteristics in Al-Si based alloys. Based on the solidification curves and microstructural examination of the corresponding alloys, it was found that addition of La or Ce increases the alloy melting temperature and the Al-Si eutectic temperature, with an Al-Si recalescence of 2-3°C, and the appearance of post-α-Al peaks attributed to precipitation of rare earth intermetallics. Addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The enrichment of Ce elements at the frontiers of the solid-liquid interface also decreased the diffusion rate of Mg and Si atoms from α-Al lattice to the liquid phase, thereby reducing the efficiency of solute redistribution [21]. Thus, the nucleation and growth of Mg 2 Si in the 5182 Al alloy was retarded, which caused the breakage of the Mg 2 Si network in the 5182-0.4Ce Al alloy (Figure 5a,b).…”
Section: Effect Of Ce-rich Mischmetal On Microstructure Evolutionmentioning
confidence: 99%
“…The enrichment of Ce elements at the frontiers of the solid-liquid interface also decreased the diffusion rate of Mg and Si atoms from α-Al lattice to the liquid phase, thereby reducing the efficiency of solute redistribution [21]. Thus, the nucleation and growth of Mg 2 Si in the 5182 Al alloy was retarded, which caused the breakage of the Mg 2 Si network in the 5182-0.4Ce Al alloy (Figure 5a,b).…”
Section: Effect Of Ce-rich Mischmetal On Microstructure Evolutionmentioning
confidence: 99%
“…Sharma et al [16] prepared the Al-11Si-20Cu brazing alloy containing La 2 O 3 by the electromagnetic induction casting process and found that the addition of La 2 O 3 significantly improved the filler brazeability, microhardness, joint tensile shear strength, and elongation of the composites. Elgallad et al [17] found that adding rare earth elements, La or Ce, to the Al-Si alloy increased the melting temperature of the alloy and caused partial modification of the eutectic Si particles. Liu et al [18] added different contents of CeO 2 and Y 2 O 3 (2 vol% and 3 vol%) to Ti/Al 2 O 3 composites prepared by vacuum hot pressing sintering to restrain the interface reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Si casting alloys have been used for a variety of purposes in the automotive and aircraft industries, due to their low density, superior castability, corrosion resistance, high strength to weight ratio, ease of recycling, high efficiency, and high wear resistance [1]. It is well known that the morphology of eutectic Si greatly affects the mechanical properties of cast Al-Si alloys [2,3]. Coarse primary Si and long needle-like eutectic Si affect the machinability of Al-Si alloys.…”
Section: Introductionmentioning
confidence: 99%